A poly-l-dlactic acid graft copolymer, and a preparation method and application thereof
Patent Information
- Application Number
- CN202310813171.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-07-05
AI Technical Summary
[0004]聚乳酸存在脆性大、疏水性强,韧性低等缺点,因此聚乳酸材料很难像聚乙烯、聚丙烯等通用塑料直接来制备工业化产品,必须对其进行改性加工
[0035] (1) Compared with the prior art, the present invention provides a novel route for synthesizing polyLD lactic acid graft copolymers. First, maleic anhydride (MA) is polymerized with L-lactide (LLA) and D-lactide (DLA) to obtain maleic anhydride and lactide copolymers MA-LLA and MA-DLA. Then, MA-LLA and MA-DLA are prepolymerized at low temperature to obtain MA-LDLA oligomers. Finally, high-temperature polymerization is carried out to obtain high molecular weight maleic anhydride grafted polyLD lactic acid copolymers.
Smart Images

Figure CN119264389B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technology of ring-opening polymerization of lactide to synthesize polylactic acid, and particularly to the preparation method of high molecular weight poly(LD) lactic acid graft copolymer, belonging to the field of polymer material synthesis. Background Technology
[0002] With the continuous development of the economy and society, people's production and life are becoming increasingly dependent on fossil energy. However, non-renewable energy sources such as oil and coal are currently in short supply, and the consumption of these energy sources causes serious environmental pollution. Petroleum-based materials are non-degradable, therefore, it is necessary to find green resources to replace oil to alleviate the pressure of resource shortages. Consequently, research on bio-based composite materials has become a hot topic in academia and industrial production in recent years, aiming to reduce the harm to the natural environment caused by the consumption of fossil energy. Compared with polyolefins and polyethylene terephthalate (PET), which are commonly used in industrial products, polylactic acid (PLA) has better strength and processing performance. It is a thermoplastic resin produced by polymerizing lactic acid monomers, which can be produced through the fermentation of plants such as corn, potatoes, cotton, and hemp. The raw materials are renewable, and it has advantages such as high strength, good processability, and excellent mechanical properties. However, PLA also has some drawbacks, such as high brittleness, strong hydrophobicity, low impact strength, and high price. Furthermore, PLA has poor stability at high temperatures and certain humidity levels, which limits its application range.
[0003] Currently, there are two main technologies for preparing polylactic acid (PLA) both domestically and internationally: the one-step method and the two-step method. The one-step method uses protic acid or metal oxide catalysts to directly polymerize lactic acid under vacuum and heating conditions. This method produces PLA with a low molecular weight, making it unsuitable for industrial applications. Industrially, the two-step method is more commonly used. In the first step, lactic acid is reacted with a catalyst to form lactide. In the second step, ring-opening polymerization is performed under reduced pressure and with a catalyst to produce PLA. High-optical-purity PLA materials are then obtained through purification techniques. There are many key factors affecting the preparation of polylactic acid (PLA). First, the optical purity of the lactide raw material used to synthesize PLA must be no less than 99%. In addition, residual free acid and water molecules during the lactide preparation process can also affect the polymerization of PLA. Second, the polymerization mechanism of PLA from lactide can be divided into cationic ring-opening polymerization, anionic ring-opening polymerization, and coordination polymerization. Different catalysts will result in different polymerization methods. Under high-temperature reaction conditions, the ring-opening polymerization of lactide to PLA is prone to racemization and oxidation reactions, which have a certain impact on the purity of the product. Finally, residual lactide monomers that have not participated in the ring-opening polymerization in the PLA product need to be removed in a timely manner, otherwise it will affect the purity and molecular weight of the PLA product.
[0004] Polylactic acid (PLA) suffers from drawbacks such as high brittleness, strong hydrophobicity, and low toughness. Therefore, PLA materials are difficult to directly manufacture industrial products like general-purpose plastics such as polyethylene and polypropylene, and must undergo modification. Currently, a common method is to blend PLA with other plastics to optimize its performance. While this method is simple, it doesn't fundamentally change the properties of PLA. Furthermore, some research focuses on modifying PLA itself, such as through grafting. Maleic anhydride is a good grafting modifier. Maleic anhydride is a polar monomer with a five-membered ring structure. Grafting PLA with maleic anhydride can improve its polarity and, due to its cyclic structure, simultaneously modify the toughness of the PLA macromolecular chains. Currently, the most common method used both domestically and internationally is to graft maleic anhydride onto polyethylene, polystyrene, starch, lignin, etc., and then add it to polylactic acid (PLA) materials through blending to improve PLA's toughness. However, the modification effect of this method is not significant. Some studies have used reactive extrusion to directly graft maleic anhydride onto PLA macromolecular chains, thereby changing the nonpolar structure of PLA. Although this method is simple, the grafting rate is low and the modification effect is not significant.
[0005] In patent FR2916203A1, a certain amount of polylactic acid (PLA) particles and maleic anhydride monomers are mixed and added to a screw extruder. Under the protection of an initiator and inert gas, high-temperature reactive extrusion is performed to prepare maleic anhydride-grafted PLA. Although maleic anhydride-grafted PLA material was successfully prepared by screw extrusion reaction, the grafting rate was less than 1%, and the modification effect on PLA material was generally limited. In patent CN105315412A, a certain amount of DL-lactide and glycolide are polymerized at high temperature under the action of a catalyst to prepare poly(lactic-co-glycolic acid). After purification, it is mixed with maleic anhydride, and maleic anhydride-grafted PLA is prepared by melt grafting in a reactor under the action of an initiator. This technology first prepares poly(lactic-co-glycolic acid) and then performs a melt maleic anhydride grafting reaction on poly(lactic-co-glycolic acid). Although maleic anhydride-grafted PLA was successfully prepared on poly(lactic-co-glycolic acid), the maleic anhydride grafting rate was less than 2%. In Chinese patent CN103570884A, crude poly(propylene glycol) (MPLGA) is prepared by using L / D-lactide, glycolide, and maleic anhydride stannous octoate as catalysts. After purification, refined MPLGA is obtained. The advantage is that the prepared polymer has a narrow molecular weight distribution. However, during the polymerization process, maleic anhydride grafting reaction occurs simultaneously, resulting in a low grafting rate and a long polymerization time. The polymer has a low molecular weight, which is not conducive to industrial production.
[0006] In summary, the current processes for preparing and modifying polylactic acid (PLA) mainly have the following problems: (1) Pure PLA products have poor heat resistance and low toughness, requiring modification for industrial application. (2) Simply adding plasticizers and toughening agents to PLA materials cannot fundamentally improve the thermodynamic properties of PLA. (3) Grafting or esterification reactions on the side chains or end groups of PLA macromolecules result in low reactivity and poor modification effects. (4) Due to the regular structure of poly-L-lactic acid and the steric hindrance in the side chain structure, grafting modification of poly-L-lactic acid alone is quite difficult. Summary of the Invention
[0007] To address the above shortcomings, this invention provides a poly(LD) lactic acid graft copolymer and its preparation method. By employing a reaction route different from existing technologies, a high molecular weight maleic anhydride-grafted poly(LD) lactic acid copolymer material (MA-PLDLA) is prepared. The maleic anhydride grafting rate is high, and the MA-PLDLA material has both good toughness and heat resistance. It is also green, biodegradable, and easy to industrialize.
[0008] To achieve the above technical objectives, the technical solution adopted by this invention is as follows:
[0009] The first aspect of the present invention aims to provide a poly(LD) lactic acid graft copolymer, which is a compound having the structure of general formula I:
[0010]
[0011] Where R1, R2, ... and R n Each independently selected from H or And R1, R2, ... and R n In the diagram, R1, R2, ... and R n for The molar percentage is not less than 15%, preferably 15%-85%, more preferably 20%-80%, further preferably 30%-70%, and most preferably 40%-60%.
[0012] Furthermore, the weight-average molecular weight of the poly(LD) lactic acid graft copolymer is 1.5 × 10⁻⁶. 5 -4.5×10 5 2.0×10 is preferred. 5 -4.0×10 5 .
[0013] Furthermore, the right-angle tear strength of the polyLD lactic acid graft copolymer is not less than 130 kN / m, preferably 140-160 kN / m; the elongation at break is not less than 35%, preferably 40-60%; and the glass transition temperature is 90-110℃.
[0014] In this invention, the right-angle tear strength and elongation at break are measured by a universal mechanical testing machine; the weight-average molecular weight is measured by gel chromatography; and the glass transition temperature is measured by differential scanning calorimetry. These are described in detail below.
[0015] The second aspect of the present invention aims to provide a method for preparing poly(LD) lactic acid graft copolymer, comprising the following:
[0016] (1) L-lactide, maleic anhydride and initiator were mixed and reacted to obtain maleic anhydride-grafted L-lactide (MA-LLA), and the product was purified; D-lactide, maleic anhydride and initiator were mixed and reacted to obtain maleic anhydride-grafted D-lactide (MA-DLA), and the product was purified.
[0017] (2) The MA-LLA, MA-DLA, catalyst and initiator obtained in (1) are mixed and prepolymerized at low temperature to obtain MA-LDLA oligomers;
[0018] (3) The MA-LDLA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain maleic anhydride-grafted poly(LD) lactic acid copolymer material (MA-PLDLA).
[0019] Further, the initiator in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxide)hexane, preferably dicumyl peroxide; the amount of initiator added by weight is 0.1-5% of L-lactide or D-lactide, preferably 0.5-2.0%.
[0020] Furthermore, step (1) is carried out under constant temperature reaction conditions with an inert gas flow, preferably nitrogen gas flow, and vacuum conditions. The reaction temperature is 50-150℃, preferably 80-120℃, and the reaction pressure is 2-100kPa, preferably 20-60kPa. The reaction time is 0.5-10h, preferably 2-6h. The gas flow rate under nitrogen gas protection is 0.5-6m / s, preferably 2-4m / s. The amount of maleic anhydride added is 100-300% of the weight of L-lactide or D-lactide, preferably 150-200%.
[0021] Furthermore, the optical purity of the L-lactide and D-lactide mentioned in step (1) is 99.0-99.6%, preferably 99.4-99.6%, and can be self-made or purchased L-lactide and D-lactide.
[0022] The main reaction that occurs in step (1) is shown in the following equation:
[0023]
[0024] Furthermore, the purification in step (1) involves removing unreacted L-lactide and D-lactide by vacuum distillation to obtain purified maleic anhydride-grafted L-lactide (MA-LLA) and maleic anhydride-grafted D-lactide (MA-DLA). Specifically, the vacuum distillation temperature is 100-200℃, preferably 120-150℃; the pressure is 0-100 kPa, preferably 10-50 kPa; and the time is 1-10 h, preferably 2-6 h.
[0025] Furthermore, the catalyst in step (2) is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride, preferably stannous octoate; the initiator is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine, preferably triphenylphosphine.
[0026] Furthermore, in step (2), the amount of MA-DLA added is 20-120% of MA-LLA, preferably 40-100%, based on the weight of MA-LLA; the amount of catalyst added is 0.2-10% of MA-LLA, preferably 1-6%; and the amount of initiator added is 0.1-10% of MA-LLA, preferably 1-5%.
[0027] Furthermore, step (2) involves low-temperature polymerization under inert gas flow, preferably nitrogen gas flow, and negative pressure conditions. The polymerization temperature is 100-150℃, preferably 120-140℃; the reaction time is 2-15h, preferably 3-8h; the reaction pressure is 100-1000kpa, preferably 200-500kpa; and the gas flow rate of the nitrogen gas flow is 0.5-6m / s, preferably 2-4m / s.
[0028] Furthermore, the antioxidant mentioned in step (3) is one of phosphite esters, alkyl polyphenols and thiobisphenols, preferably triphenyl phosphite, and the amount of antioxidant added is 1%-10% of MA-LLA oligomer by weight, preferably 2-6%.
[0029] Furthermore, the polymerization temperature in step (3) is 150-250℃, preferably 160-200℃.
[0030] Furthermore, in step (3), a twin-screw extruder is used to carry out the reaction process. MA-LLA oligomer, MA-DLA oligomer and antioxidant are added to the twin-screw extruder for polymerization reaction, high-temperature reactive compounding, extrusion and granulation are performed, and finally maleic anhydride grafted poly(LD) lactic acid copolymer material (MA-PLDLA) is obtained.
[0031] The main reaction processes in steps (2) and (3) are shown in the following equations:
[0032]
[0033] The technical objective of the third aspect of this invention is to provide applications of the above-mentioned polyLD lactic acid graft copolymer, which is used in fields such as agricultural mulch film, food packaging, and medical and hygiene products.
[0034] Compared with existing technologies, the present invention has the following advantages:
[0035] (1) Compared with the prior art, the present invention provides a novel route for synthesizing polyLD lactic acid graft copolymers. First, maleic anhydride (MA) is polymerized with L-lactide (LLA) and D-lactide (DLA) to obtain maleic anhydride and lactide copolymers MA-LLA and MA-DLA. Then, MA-LLA and MA-DLA are prepolymerized at low temperature to obtain MA-LDLA oligomers. Finally, high-temperature polymerization is carried out to obtain high molecular weight maleic anhydride grafted polyLD lactic acid copolymers.
[0036] (2) The method of the present invention performs a grafting reaction of maleic anhydride before the polymerization of lactide, which greatly improves the grafting efficiency and increases the molecular weight of the polymer. More maleic anhydride polar groups are successfully introduced into the side chain of polyLD lactic acid through the grafting reaction, which improves the toughness and elongation at break of polyLD lactic acid material.
[0037] (3) The present invention solves the problem of the difficulty and low grafting rate of introducing maleic anhydride groups onto the side chains of poly-L-lactic acid due to the regular structure of poly-L-lactic acid and the steric hindrance on the side chain structure. By adding a portion of maleic anhydride-grafted D-lactide and maleic anhydride-grafted L-lactide for copolymerization, the present invention solves the problem of the difficulty and low grafting rate of introducing maleic anhydride groups onto the side chains of poly-L-lactic acid due to the regular structure of poly-L-lactic acid and the steric hindrance on the side chain structure.
[0038] (4) The product of the present invention retains the terminal hydroxyl groups of the graft copolymer, thereby enabling it to be further modified through the functional group to further regulate the properties of the copolymer.
[0039] (5) Due to the introduction of a large number of maleic anhydride cyclic structures on the side chains of polyLD lactic acid, the glass transition temperature of polyLD lactic acid material is increased, and the prepared graft-modified polyLD lactic acid copolymer material is green and fully biodegradable.
[0040] (6) The bulk prepolymerization reaction of L-lactide is carried out in a reaction vessel and coupled with a twin-screw extruder for copolymerization. The reaction operation is simple and easy to industrialize.
[0041] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation
[0042] The following non-limiting embodiments are intended to enable those skilled in the art to more fully understand the present invention, but do not limit the invention in any way. Unless otherwise specified, the reagents, materials, and instruments involved in the following embodiments can be obtained through legitimate commercial channels. Unless otherwise specified, the testing and inspection methods involved in the following embodiments are existing testing and inspection methods in the prior art. The following embodiments clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All obvious variations or modifications derived from the present invention still fall within the scope of protection of the present invention.
[0043] The following are the test methods for performance parameters involved in the embodiments:
[0044] (1) Grafting rate of grafted groups:
[0045] The grafting rate of grafted groups in polylactic acid graft copolymers was determined by chemical titration. Specifically, a certain mass of polylactic acid graft copolymer was weighed and placed in an Erlenmeyer flask, a certain amount of tetrahydrofuran was added to dissolve it, and a small amount of thymol blue / DMF indicator was added. The solution was titrated with an excess of 0.05 mol / L potassium hydroxide in ethanol solution and back-titrated with 0.01 mol / L HCl-isopropanol solution.
[0046] Grafting rate = n2 / n1 × 100%, n1 = (m0 - m2) / M1, n2 = m2 / M2, that is, grafting rate = [(0.05V KOH -0.01V HCl )×2×M1] / [m0-(0.05V KOH -0.01V HCl [m0] × 2 × M2; where m0 is the mass of the polylactic acid graft copolymer weighed, in g; m2 is the total mass of the grafted groups on the polylactic acid molecular chain, calculated based on the consumed KOH; n1 is the degree of polymerization of polylactic acid, i.e., the amount of substance of lactic acid unit; n2 is the amount of substance of the grafted groups on the polylactic acid molecular chain; M1 is the molar mass of lactic acid; M2 is the molar mass of the grafted groups; V KOH V represents the volume of potassium hydroxide ethanol solution added, in mL; HCl The volume of HCl-isopropanol solution consumed in the titration is expressed in mL.
[0047] (2) Right-angle tear strength and elongation at break: measured by a universal testing machine in accordance with GB / T1039-1992 standard.
[0048] (3) Glass transition temperature: Measured using a differential scanning calorimeter (DSC) (DSC 204, Netzsch, Germany). The test conditions were as follows: 5–10 mg of sample was heated from room temperature to 200 °C at a heating rate of 10 °C / min and held at isothermal temperature for 5 min to eliminate the thermal history of the sample; then the sample was rapidly cooled to -20 °C, and then heated from -20 °C to 200 °C at a heating rate of 10 °C / min; nitrogen gas was introduced as a protective gas throughout the test, with a flow rate of 50 mL / min.
[0049] (4) Polymer weight-average molecular weight: Measured by gel permeation chromatography (GPC). The molecular weight of the polylactic acid graft copolymer samples was characterized using gel permeation chromatography (GPC Waters 1515 system). Chromatographically pure THF was used as the mobile phase at a flow rate of 1.0 mL / min and a column temperature of 35 °C. Before testing, the sample was dissolved in THF at a concentration of 5 mg / mL, filtered through a 0.22 μm polytetrafluoroethylene (PTFE) membrane, and injected. Calibration was performed using narrow-distribution polystyrene (PS) standards.
[0050] (5) Detection of terminal hydroxyl groups: The phthalic anhydride method was used to determine the hydroxyl groups according to the standard GB / T 12008.3-2009.
[0051] Example 1
[0052] (1) L-lactide and maleic anhydride were added to a reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted L-lactide polymer. D-lactide and maleic anhydride were added to another reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted D-lactide polymer. The reaction temperature for both grafting modifications was 95℃, the reaction pressure was 35kPa, and the reaction time was 2h. The gas flow rate under nitrogen protection was 2m / s. The amount of maleic anhydride added was 150% of the weight of L-lactide or D-lactide, and the amount of dicumyl peroxide was 0.5% of the weight of L-lactide or D-lactide.
[0053] (2) The L-lactide and D-lactide that did not participate in the grafting reaction in step (1) were removed by vacuum distillation to obtain purified maleic anhydride-grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature was 125℃, the pressure was 15kpa, and the time was 2h.
[0054] (3) The MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, with the addition of nitrogen gas flow and negative pressure to obtain MA-LLA oligomer and MA-DLA oligomer respectively; the reaction temperature of the low temperature prepolymerization is 130℃, the reaction time is 3h, the reaction pressure is 300kpa, the gas flow rate of the nitrogen gas flow protection is 3m / s, and the catalyst stannous octoate is 1% of MA-LLA or MA-DLA by weight; the initiator triphenylphosphine is 1% of MA-LLA or MA-DLA.
[0055] (4) The MA-LLA oligomer and MA-DLA oligomer from step (3) are simultaneously added to a twin-screw extruder for polymerization reaction. Antioxidant is added at the same time, and the mixture is subjected to high-temperature reactive compounding, extrusion and granulation to finally obtain maleic anhydride grafted poly(LD) lactic acid copolymer material (MA-PLDLA). Based on the weight of MA-LLA oligomer, MA-DLA is 30% of MA-LLA, and the antioxidant triphenyl phosphite is 2% of MA-LLA oligomer. The reactive extrusion temperature for reactive compounding, extrusion and granulation in the twin-screw extruder is 180°C.
[0056] Performance characterization: The right-angle tear strength of the maleic anhydride-grafted poly(LD) lactic acid copolymer was measured to be 140 kN / m, the elongation at break was 38%, the glass transition temperature was 93℃, and the molecular weight of the polymer was 2.80 × 10⁻⁶. 5 The maleic anhydride grafting rate of the polymer was determined to be 46.1% by chemical titration, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.
[0057] Example 2
[0058] (1) L-lactide and maleic anhydride were added to a reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted L-lactide polymer. D-lactide and maleic anhydride were added to another reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted D-lactide polymer. The reaction temperature for both grafting modifications was 100℃, the reaction pressure was 35 kPa, the reaction time was 3 h, and the gas flow rate under nitrogen protection was 2.5 m / s. Based on the weight of L-lactide / D-lactide, maleic anhydride accounted for 160% of L-lactide / D-lactide, and dicumyl peroxide accounted for 1.0% of L-lactide / D-lactide.
[0059] (2) The L-lactide and D-lactide that did not participate in the grafting reaction in step (1) were removed by vacuum distillation to obtain purified maleic anhydride-grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature was 130℃, the pressure was 15kpa, and the time was 2.5h.
[0060] (3) The MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, with the addition of nitrogen gas flow and negative pressure to obtain MA-LLA oligomers and MA-DLA oligomers respectively. The reaction temperature of the low-temperature prepolymerization is 135°C, the reaction time is 4h, the reaction pressure is 350kpa, the gas flow rate of the nitrogen gas flow protection is 3m / s, and the catalyst stannous octoate is 2% of MA-LLA or MA-DLA by weight; the initiator triphenylphosphine is 2% of MA-LLA or MA-DLA.
[0061] (4) The MA-LLA oligomer and MA-DLA oligomer from step (3) are simultaneously added to a twin-screw extruder for polymerization reaction. Antioxidant is added at the same time, and the mixture is subjected to high-temperature reactive compounding, extrusion and granulation to finally obtain maleic anhydride grafted poly(LD) lactic acid copolymer material (MA-PLDLA). Based on the weight of MA-LLA oligomer, MA-DLA is 40% of MA-LLA, and the antioxidant triphenyl phosphite is 3% of MA-LLA oligomer. The reactive extrusion temperature for reactive compounding, extrusion and granulation in the twin-screw extruder is 180°C.
[0062] Performance characterization: The right-angle tear strength of the maleic anhydride-grafted poly(LD) lactic acid copolymer was measured to be 145 kN / m, the elongation at break was 41%, the glass transition temperature was 96 °C, and the molecular weight of the polymer was 3.03 × 10⁻⁶. 5 The maleic anhydride grafting rate of the polymer was determined to be 50.3% by chemical titration, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.
[0063] Example 3
[0064] (1) L-lactide and maleic anhydride were added to a reactor, and dicumyl peroxide was added as an initiator. The reactor was subjected to a constant temperature reaction under nitrogen flow and vacuum conditions to obtain a maleic anhydride-grafted L-lactide polymer. D-lactide and maleic anhydride were added to another reactor, and dicumyl peroxide was added as an initiator. The reactor was subjected to a constant temperature reaction under nitrogen flow and vacuum conditions to obtain a maleic anhydride-grafted D-lactide polymer. The reaction temperature for the above two grafting modifications was 100℃, the reaction pressure was 40kPa, the reaction time was 3h, and the gas flow rate under nitrogen protection was 3m / s. Based on the weight of L-lactide or D-lactide, the amount of maleic anhydride added was 170% of the weight of L-lactide or D-lactide, and the amount of dicumyl peroxide was 1.0% of the weight of L-lactide or D-lactide.
[0065] (2) The L-lactide and D-lactide that did not participate in the grafting reaction in step (1) were removed by vacuum distillation to obtain purified maleic anhydride-grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature was 130℃, the pressure was 20 kPa, and the time was 3 h.
[0066] (3) The MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, with the addition of nitrogen gas flow and negative pressure to obtain MA-LLA oligomers and MA-DLA oligomers respectively. The reaction temperature of the low-temperature prepolymerization is 135°C, the reaction time is 4.5h, the reaction pressure is 350kpa, the gas flow rate of the nitrogen gas flow protection is 3.5m / s, and the catalyst stannous octoate is 3% of MA-LLA or MA-DLA by weight; the initiator triphenylphosphine is 3% of MA-LLA / MA-DLA.
[0067] (4) The MA-LLA oligomer and MA-DLA oligomer from step (3) are simultaneously added to a twin-screw extruder for polymerization reaction. Antioxidant is added at the same time, and the mixture is subjected to high-temperature reactive compounding, extrusion and granulation to finally obtain maleic anhydride grafted poly(LD) lactic acid copolymer material (MA-PLDLA). Based on the weight of MA-LLA oligomer, MA-DLA is 50% of MA-LLA, and the antioxidant triphenyl phosphite is 4% of MA-LLA oligomer. The reactive extrusion temperature for reactive compounding, extrusion and granulation in the twin-screw extruder is 185°C.
[0068] Performance characterization: The right-angle tear strength of the maleic anhydride-grafted poly(LD) lactic acid copolymer was measured to be 152 kN / m, the elongation at break was 48%, the glass transition temperature was 99 °C, and the molecular weight of the polymer was 3.25 × 10⁻⁶. 5 The maleic anhydride grafting rate of the polymer was determined to be 53.4% by chemical titration, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.
[0069] Example 4
[0070] (1) L-lactide and maleic anhydride were added to a reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted L-lactide polymer. D-lactide and maleic anhydride were added to another reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted D-lactide polymer. The reaction temperature for the two grafting modifications was 105℃, the reaction pressure was 45kpa, the reaction time was 3.5h, and the gas flow rate under nitrogen protection was 3m / s. Based on the weight of L-lactide or D-lactide, maleic anhydride was 180% of L-lactide or D-lactide, and dicumyl peroxide was 1.5% of L-lactide or D-lactide.
[0071] (2) The L-lactide and D-lactide that did not participate in the grafting reaction in step (1) were removed by vacuum distillation to obtain purified maleic anhydride-grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature was 130℃, the pressure was 25 kPa, and the time was 3.5 h.
[0072] (3) The MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, with the addition of nitrogen gas flow and negative pressure to obtain MA-LLA oligomers and MA-DLA oligomers respectively. The reaction temperature of the low-temperature prepolymerization is 140℃, the reaction time is 4.5h, the reaction pressure is 350kpa, the gas flow rate of the nitrogen gas flow protection is 3.5m / s, and the catalyst stannous octoate is 4% of MA-LLA or MA-DLA by weight; the initiator triphenylphosphine is 4% of MA-LLA or MA-DLA.
[0073] (4) The MA-LLA oligomer and MA-DLA oligomer from step (3) are simultaneously added to a twin-screw extruder for polymerization reaction. Antioxidant is added at the same time, and the mixture is subjected to high-temperature reactive compounding, extrusion and granulation to finally obtain maleic anhydride grafted poly(LD) lactic acid copolymer material (MA-PLDLA). Based on the weight of MA-LLA oligomer, MA-DLA is 60% of MA-LLA, and the antioxidant triphenyl phosphite is 5% of MA-LLA oligomer. The reactive extrusion temperature for reactive compounding, extrusion and granulation in the twin-screw extruder is 185°C.
[0074] Performance characterization: The right-angle tear strength of the maleic anhydride-grafted poly(LD) lactic acid copolymer was measured to be 160 kN / m, the elongation at break was 57%, the glass transition temperature was 104 °C, and the molecular weight of the polymer was 3.48 × 10⁻⁶.5 The maleic anhydride grafting rate of the polymer was determined to be 58.6% by chemical titration, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.
[0075] Example 5
[0076] (1) L-lactide and maleic anhydride were added to a reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted L-lactide polymer. D-lactide and maleic anhydride were added to another reaction vessel, and dicumyl peroxide was added as an initiator. The reaction was carried out under constant temperature conditions with nitrogen flow and vacuum to obtain a maleic anhydride-grafted D-lactide polymer. The reaction temperature for the two grafting modifications was 110°C, the reaction pressure was 55 kPa, the reaction time was 4 h, and the gas flow rate under nitrogen protection was 4 m / s. Based on the weight of L-lactide or D-lactide, maleic anhydride was 200% of L-lactide or D-lactide, and dicumyl peroxide was 2.0% of L-lactide or D-lactide.
[0077] (2) The L-lactide and D-lactide that did not participate in the grafting reaction in step (1) were removed by vacuum distillation to obtain purified maleic anhydride-grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature was 135℃, the pressure was 30 kPa, and the time was 3.5 h.
[0078] (3) The MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, with the addition of nitrogen gas flow and negative pressure to obtain MA-LLA oligomer and MA-DLA oligomer respectively; the reaction temperature of the low temperature prepolymerization is 140℃, the reaction time is 5h, the reaction pressure is 400kpa, the gas flow rate of the nitrogen gas flow protection is 4m / s, and the catalyst stannous octoate is 6% of MA-LLA or MA-DLA by weight; the initiator triphenylphosphine is 5% of MA-LLA or MA-DLA.
[0079] (4) The MA-LLA oligomer and MA-DLA oligomer from step (3) are simultaneously added to a twin-screw extruder for polymerization reaction. Antioxidant is added at the same time, and the mixture is subjected to high-temperature reactive compounding, extrusion and granulation to finally obtain maleic anhydride grafted poly(LD) lactic acid copolymer material (MA-PLDLA). Based on the weight of MA-LLA oligomer, MA-DLA is 80% of MA-LLA, and the antioxidant triphenyl phosphite is 6% of MA-LLA oligomer. The reactive extrusion temperature for reactive compounding, extrusion and granulation in the twin-screw extruder is 190°C.
[0080] Performance characterization: The right-angle tear strength of the maleic anhydride-grafted poly(LD) lactic acid copolymer was measured to be 148 kN / m, the elongation at break was 44%, the glass transition temperature was 97℃, and the molecular weight of the polymer was 3.12 × 10⁻⁶. 5 The maleic anhydride grafting rate of the polymer was determined to be 51.5% by chemical titration, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.
[0081] Comparative Example 1
[0082] Polylactic acid graft copolymers are prepared using existing techniques that first polymerize L-lactide or D-lactide and then graft them.
[0083] (1) L-lactide (LLA) was prepolymerized at low temperature under the action of a catalyst and initiator, and under nitrogen flow and negative pressure conditions to obtain LLA oligomers. The reaction temperature for low-temperature prepolymerization was 130℃, the reaction time was 3h, the reaction pressure was 300kPa, the flow rate of the nitrogen flow was 3m / s, and the amount of stannous octoate catalyst added was 0.5wt% of the amount of LLA, and the amount of triphenylphosphine initiator added was 0.2wt% of the amount of LLA.
[0084] (2) Replace L-lactide (LLA) in step (1) with D-lactide (DLA), and keep everything else the same as in step (1) to obtain DLA oligomer.
[0085] (3) The LLA oligomer obtained in step (1) and the DLA oligomer obtained in step (2) are added to a twin-screw extruder for polymerization reaction. Maleic anhydride (MA) and antioxidant are added at the same time. The mixture is then subjected to high-temperature reactive compounding, extrusion and granulation to finally obtain maleic anhydride-grafted polylactic acid material (MA-PLLA). The DLA oligomer is 30% of the LLA oligomer. By weight, the amount of maleic anhydride added is 15wt% of the total weight of the LLA oligomer and DLA oligomer (and the inventor's experiments have verified that even if the amount of maleic anhydride added is increased, the grafting rate is not improved). The amount of antioxidant triphenyl phosphite added is 2wt% of the LLA oligomer. The reactive extrusion temperature of the twin-screw extruder for reactive compounding, extrusion and granulation is 180℃.
[0086] Product performance: The measured right-angle tear strength of the copolymer material is 102 KN / m, the elongation at break is 12%, the glass transition temperature is 68℃, and the molecular weight of the polymer is 2.45 × 10⁻⁶. 5 The maleic anhydride grafting rate of the polymer was determined to be 1.8% by chemical titration; the presence of terminal hydroxyl groups could not be detected by chemical titration.
Claims
1. A polyLD lactic acid graft copolymer, characterized in that, It is a compound with the general formula I: , Ⅰ Where R1, R2, ... and R n Selected independently from H or And R1, R2, ... and R n In the diagram, R1, R2, ... and R n for The percentage of moles is 40%-60%.
2. The copolymer according to claim 1, characterized in that, Its weight-average molecular weight is 1.5 × 10⁻⁶. 5 -4.5×10 5 .
3. The copolymer according to claim 1, characterized in that, Its right-angle tear strength is not less than 130kN / m, its elongation at break is not less than 35%, and its glass transition temperature is 90-110℃.
4. The method for preparing the poly(LD) lactic acid graft copolymer according to claim 1, comprising the following: (1) Mix L-lactide, maleic anhydride and initiator to react and obtain maleic anhydride-grafted L-lactide MA-LLA, and purify the product; mix D-lactide, maleic anhydride and initiator to react and obtain maleic anhydride-grafted D-lactide MA-DLA, and purify the product. (2) The MA-LLA, MA-DLA, catalyst and initiator obtained in (1) are mixed and prepolymerized at low temperature to obtain MA-LDLA oligomers; (3) The MA-LDLA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain maleic anhydride-grafted poly(LD) lactic acid copolymer material MA-PLDLA.
5. The preparation method according to claim 4, characterized in that, The initiator mentioned in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, and the amount of initiator added is 0.1-5% of L-lactide or D-lactide by weight.
6. The preparation method according to claim 4, characterized in that, Step (1) is carried out under constant temperature reaction conditions with inert gas flow and vacuum, with reaction temperature of 50-150℃, reaction pressure of 2-100kPa, and reaction time of 0.5-10h.
7. The preparation method according to claim 4, characterized in that, The amount of maleic anhydride added is 100-300% of the weight of L-lactide or D-lactide.
8. The preparation method according to claim 4, characterized in that, The purification described in step (1) involves removing L-lactide and D-lactide that did not participate in the grafting reaction by vacuum distillation. The vacuum distillation temperature is 100-200℃, the pressure is 0-100kpa, and the time is 1-10h.
9. The preparation method according to claim 4, characterized in that, The catalyst in step (2) is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum and stannous chloride; the initiator is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine.
10. The preparation method according to claim 4, characterized in that, In step (2), the amount of catalyst added is 0.2-10% of MA-LLA by weight, and the amount of initiator added is 0.1-10% of MA-LLA.
11. The preparation method according to claim 4, characterized in that, In step (2), the amount of MA-DLA added is 20-120% of the weight of MA-LLA.
12. The preparation method according to claim 4, characterized in that, Step (2) is low-temperature polymerization under inert gas flow and negative pressure conditions. The polymerization temperature is 100-150℃, the reaction time is 2-15h, and the reaction pressure is 100-1000kPa.
13. The preparation method according to claim 4, characterized in that, The antioxidant mentioned in step (3) is one of phosphites, alkyl polyphenols and thiobisphenols. The amount of antioxidant added is 1%-10% of the MA-LLA oligomer by weight.
14. The preparation method according to claim 4, characterized in that, The polymerization temperature in step (3) is 150-250℃.
15. The preparation method according to claim 4, characterized in that, Step (3) uses a twin-screw extruder to carry out the reaction process. MA-LLA oligomer, MA-DLA oligomer and antioxidant are added to the twin-screw extruder for polymerization reaction. High-temperature reactive compounding, extrusion and granulation are carried out to finally obtain maleic anhydride grafted poly(LD) lactic acid copolymer material.
16. The application of the polyLD lactic acid graft copolymer of claim 1, wherein the copolymer is used in the fields of agricultural mulch film, food packaging and medical and hygiene products.
Citation Information
Patent Citations
Preparation method for maleic anhydride-modified polylactic-co-glycolic acid
CN103570884A
Technology for preparing high-molecular-weight MPLGA by directly grafting maleic anhydride onto PLGA
CN105315412A
Method for modifying polylacticacid by adopting unsaturated cyclic anhydride or unsaturated cyclic imide, modified product and application
CN1367189A
Method for modifying polylactic acid by adopting unsaturated cyclic acid anhydride or unsaturated cyclic acid imide and its application
CN1495216A